2005
DOI: 10.1111/j.1365-2230.2005.01848.x
|View full text |Cite|
|
Sign up to set email alerts
|

Incontinentia pigmenti case series: clinical spectrum of incontinentia pigmenti in 53 female patients and their relatives

Abstract: A retrospective case series of 53 female patients with incontinentia pigmenti (IP) including 28 secondary cases (female relatives of probands) was reviewed and compared with other series in an attempt to estimate more accurately the true disease burden of patients with IP. We found that, while the frequency of the first three cutaneous stages of IP was comparable with previous studies, none of the secondary cases manifested any serious neurological complications but all displayed stage IV pale anhidrotic retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 31 publications
2
33
2
12
Order By: Relevance
“…Characteristic stage 4 lesions have been reported in 27 relatives of IP proband. 13 These lesions may be difficult to detect in women with light skin, but no differential diagnosis can be evoked. In a few cases, IP presents as subtle patchy hairless lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic stage 4 lesions have been reported in 27 relatives of IP proband. 13 These lesions may be difficult to detect in women with light skin, but no differential diagnosis can be evoked. In a few cases, IP presents as subtle patchy hairless lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] In adults, the clinical diagnosis of IP is principally based on the late onset of stage 4 lesions and their association with dental, nail, ocular, or central nervous system anomalies. 13,14 Even so, these lesions are often unrecognized.…”
mentioning
confidence: 97%
“…The function of NEMO, a 23-kb gene consisting of 10 exons, is to permit cells to respond to external signals such as growth factors [5]. This gene encodes a protein that regulates the function of various chemokines, cytokines and adhesion molecules, and is essential for protection against tumour necrosis factor-induced apoptosis [1,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Although there are many case reports of men with IP submitted to mutation analysis, none of these patients has been shown to carry the common NEMO deletion. Several studies have demonstrated the presence of hypomorphic NEMO alleles, a finding suggesting that less severe NEMO mutations permit the survival of affected men [6,7]. There are also several reports of men with IP who present the 47, XXY karyotype (Klinefelter syndrome) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…88,89 Several recent studies show the considerable variation of ocular findings (Table 2). 82,84,85,[90][91][92][93][94][95] Nevus of Ota Background In oculodermal melanocytosis, or nevus of Ota, a hamartoma of spindle-shaped melanocytes can be found in the skin, eyes, and central nervous system. In the skin, the lesion presents as a bluish, black patch most commonly in the areas of the dermis innervated by the first and second divisions of the trigeminal nerve.…”
Section: Incontinentia Pigmentimentioning
confidence: 99%